Challenges of Anthropocentrism in Wartime: A Legal and Normative Perspective - Riabykh, N.; Kuzenko, U.; Humeniuk, T.; Chuienko, V.; Bezushko, A.; Безушко, Андрій Петрович (Editorial Salud, Ciencia y Tecnologia, 2025)
Introduction: The topic is relevant due to the growing scale of armed conflicts and human rights violations, which endangers civilians and international security. In this context, the ideology of human-centredness, the basis for ensuring human rights and freedoms, is critical to protecting human rights during war and the stability of post-war reconstruction. Objective: This research article aims to systematise the mechanisms of human rights protection in times of war based on the concept of human centrism, analyse the existing mechanisms of human rights protection, and assess the threat to civilians in the context of Russia's full-scale invasion of Ukraine. Methods: The article uses several general scientific research methods, including synthesis, induction, deduction, comparative analysis, systematisation, and generalisation. To conduct the study, the author analysed the scientific literature and used statistical analysis to generate initial data for further forecasting the dynamics of war crimes and conducting a risk assessment for the civilian population using the statistical software Excel. Results: As a result of the study, the number of episodes of Russia's war crimes against humanity was calculated by regions of Ukraine, which allowed us to make assumptions about the future threat to these regions' populations and human rights. According to the calculations, in 2024 (baseline), the threat level is 31.4%, and in 2025 (planned), the threat level will decrease by 8.65% due to comprehensive government and military measures to prevent Russian aggression and protect civilians. Conclusions: The study identified the primary mechanisms for the protection of human rights in times of war based on the principles of human centrism, including condemnation of aggression as an act of violation of international law and violation of fundamental human rights, bringing the aggressor to justice and, if necessary, initiating an international search for persons involved in the escalation of the conflict; allowing the use of force against the aggressor state to protect the lives and fundamental rights of civilians and neutralise military threats.
Keywords: human centrism; anthropocentrism; humanism; technocracy; war crimes; human rights violations; human rights restrictions; martial law; post-war reconstruction